Clinical Manifestation of AGE-RAGE Axis in Neurodegenerative and Cognitive Impairment Disorders - Naz, Sabreena; Mahmood, Tarique; Gupta, Ramesh; Siddiqui, Mohammed Haris; Ahsan, Farogh; Ansari, Vaseem Ahamad; Shamim, Arshiya; Rizvi, Ali Abbas (Drug Research, 2023)
The receptor of Advanced Glycation Endproducts (RAGE) and Advanced Glycation Endproducts (AGE) have multiple functions in our body and their restraint are being observed in neurodegenerative and memory impairment disorders. The review of different pathways allows an understanding of the probable mechanism of neurodegeneration and memory impairment involving RAGE and AGE. Commonly we observe AGE accumulation in neural cells and tissues but the extent of accumulation increases with the presence of memory impairment disorder. The presence of AGEs can also be seen in morbid accumulation, pathological structures in the form of amyloid clots, and nervous fibrillary tangles in Alzheimer’s Disease (AD) and memory impairment disease.Many neuropathological and biochemical aspects of AD are explained by AGEs, including widespread protein crosslinking, glial activation of oxidative stress, and neuronal cell death. Oxidative stress is due to different reasons and glycation end products set in motion and form or define various actions which are normally due to AGE changes in a pathogenic cascade. By regulating the transit of ß-amyloid in and out of the brain or altering inflammatory pathways, AGE and it’s ensnare receptor such as soluble RAGE may function as blockage or shield AD development. RAGE activates the transcription-controlling factor Necrosis Factor (NF-κB) and increases the protraction of cytokines, like a higher number of Tumor Necrosis Factor (TNF-α) and Interleukin (IL-I) by inducing several signal transduction cascades. Furthermore, binding to RAGE can pro-activate reactive oxygen species (ROS), which is popularly known to cause neuronal death.
Keywords: AGE-RAGE axis; Neurodegeneration; cognitive impairment; Parkinson; Alzheimer